2020
DOI: 10.3389/fmed.2020.00021
|View full text |Cite
|
Sign up to set email alerts
|

New Developments in Transcriptomic Analysis of Synovial Tissue

Abstract: Transcriptomic technologies are constantly changing and improving, resulting in an ever increasing understanding of gene expression in health and disease. These technologies have been used to investigate the pathological changes occurring in the joints of rheumatoid arthritis patients, leading to discoveries of disease mechanisms, and novel potential therapeutic targets. Microarrays were initially used on both whole tissue and cell subsets to investigate research questions, with bulk RNA sequencing allowing fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Currently, transcriptomic and microarray analyses have been widely used in a variety of diseases, including a variety of tumours and RA, to identify new biomarkers to improve diagnosis and treatment [8][9][10][11][12]. In addition, competitive endogenous RNA (ceRNA) networks can elucidate a new mechanism for promoting the development of the disease in a transcriptional regulatory network [13].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, transcriptomic and microarray analyses have been widely used in a variety of diseases, including a variety of tumours and RA, to identify new biomarkers to improve diagnosis and treatment [8][9][10][11][12]. In addition, competitive endogenous RNA (ceRNA) networks can elucidate a new mechanism for promoting the development of the disease in a transcriptional regulatory network [13].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic and high-throughput microarray/RNA-seq analyses have been widely applied to many diseases, including COPD, to explore the mechanisms and advance diagnosis/treatment ( Kaczkowski et al, 2016 ; Macias-Segura et al, 2018 ; Demircioglu et al, 2019 ; Li et al, 2019 ; Morrow et al, 2019 ; Carr et al, 2020 ; Cheng et al, 2021 ). In addition, the competitive endogenous RNA (ceRNA) networks can also provide new insights into the mechanisms of disease development in a transcriptional regulatory network ( Salmena et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…These inflammatory mediators are produced by several types of cells in the joints, including synovial fibroblasts (SFs) [ 14 , 15 ], the dominant cells in the synovium [ 16 ]. Activated synovial fibroblasts (AFs) in the synovium regulate the influx and efflux of leukocytes and are involved in cartilage alteration [ 17 ], which in turn creates a vicious cycle that amplifies synovial inflammation through the induction of certain signaling molecules, damaging the cartilage and eventually the bone [ 11 ]. Studies have indicated that mechanical stress and elevated levels of proinflammatory cytokines in OA-affected joints disrupt osteoclast differentiation [ 18 ] and play a causative role in upsetting the critical balance between anabolic and catabolic signals in cartilage homeostasis [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%